1987
DOI: 10.1007/bf00609957
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the pharmacokinetics and pharmacodynamics of atenolol, hydrochlorothiazide and amiloride in normal young and elderly subjects and elderly hypertensive patients

Abstract: Six normal young and six normal elderly volunteers and six elderly hypertensive patients took part in an acute and chronic dose study of a combination capsule containing atenolol (50 mg), hydrochlorothiazide (25 mg) and amiloride (2.5 mg) designed for the treatment of hypertension. No difference in any of the drug pharmacokinetic parameters could be detected between the hypertensives and the normal elderly subjects. The bio-availability and the 24-h blood concentrations of all three drugs, half-life of atenolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…However, the incidence of hyperkalaemia with these drugs increases with age, particularly in the presence of renal impairment (Lawson 1974). Increased plasma amiloride concentrations (Sabanathan et al 1987;Somogyi et al 1990) associated with age-related reductions in urinary potassium excretion have recently been demonstrated. No data were available on serum potassium concentrations (Somogyi et al 1990).…”
Section: Potassium-sparing Diureticsmentioning
confidence: 98%
“…However, the incidence of hyperkalaemia with these drugs increases with age, particularly in the presence of renal impairment (Lawson 1974). Increased plasma amiloride concentrations (Sabanathan et al 1987;Somogyi et al 1990) associated with age-related reductions in urinary potassium excretion have recently been demonstrated. No data were available on serum potassium concentrations (Somogyi et al 1990).…”
Section: Potassium-sparing Diureticsmentioning
confidence: 98%
“…A slight reduction in the renal clearance of thiazide diuretics and triamterene, alone or in combination, has also been observed with advancing age [101,102]. The latter findings have been disproved by a recent study [77].…”
Section: Diureticsmentioning
confidence: 99%
“…Several studies have reported that peak plasma levels occur 4 hr after oral administration, absorption ranges from 90% to 95% of the dose and half-life ranges from 10-14 hr. [2][3][4][5] Since amiloride exhibits an extremely low therapeutic range (0.5-25 ng/mL), only a few sufficiently specific and sensitive HPLC methods for pharmacokinetic studies have been described. [6][7][8][9][10][11] The pharmacokinetics and bioavailability of amiloride in plasma and/or urine have been investigated by determining its levels by fluorometric, 12 radioactive, 13 densitofluorimetric, 14 or spectrometric 15 assays.…”
Section: Amiloridementioning
confidence: 99%